Mapping and analysing tradeoffs, synergies and losses among multiple ecosystem services across a transitional area in Beijing, China - Long Chen (Elsevier, 2021)
Understanding the complex relationships among ecosystem services (ESs) is a prerequisite for optimized management and is of great significance to China’s current implementation of an eco-civilization. However, it is always difficult to simultaneously reveal the relationships among multiple ESs from a local perspective. We proposed an assessment framework that can quantify and conveniently display the intensities of relationships (tradeoffs, synergies, and losses) among multiple ESs, permitting the spatial heterogeneity and gradient effects of these relationships to be revealed. Using township as the study unit, a case study was conducted and nine ESs were evaluated in a transitional area, the Beijing Bay Area (BBA), where the conflict between conservation and development has been prominent. The results suggested that nine ESs were clumped and showed either a high-low (ecosystem-dominated ESs) or a low-high (human-dominated ESs) spatial pattern from northwest to southeast in the BBA. In addition, the relationships among multiple ESs showed significant spatial heterogeneity across townships. In general, tradeoff intensity was mainly related to the supply of human-dominated ESs (especially food supply or water quality regulation), and synergy intensity and loss intensity were mainly related to the supply of ecosystem-dominated ESs. Moreover, all relationships among multiple ESs showed gradient effects along influencing factors. The tradeoff intensity largely exhibited V-shaped patterns, first decreasing and then increasing. Synergy intensity and loss intensity were mainly characterized by monotonically increasing or decreasing patterns. Overall, we found that the process of formation of ESs and their dominating factors largely determined their spatial patterns, spatial heterogeneity, and the gradient effects along influencing factors within the BBA. Based on these results, we propose optimized management suggestions for different townships, combining new plans for development of the BBA. The results of our study will provide information for policy makers to alleviate conflict between conservation and development and will promote sustainable development in the area.